Administration and law in the Tibetan Empire - Dotson, B (2007)
﻿ The present study consists of a full translation and analysis of the three main versions of the Section on Law and State, a chapter on Tibetan imperial law and administration found in the mid-16th century Mkhas pa'i dga' ston by Dpa'-bo Gtsuglag Phreng-ba, and in the Rgya bod kyi chos 'byung rgyas pa of Mkhas-pa Lde'u and the Chos 'byung chen po bstan pa'i rgyal mtshan of Lde'u Jo-sras, which both date to the mid to late-13th century. While the post-dynastic Tibetan historical tradition attributes this entire body of legal and administrative reforms to Emperor Srong-btsan Sgam-po (c.605-649), the individual legal and administrative catalogues contained in the Section on Law and State, when subjected to close analysis, can be dated to several different periods. The principal aim of this analysis is to underline the early Tibetan antecedents for the catalogues contained in the Section on Law and State. By relating the catalogues of the Section on Law and State to Old Tibetan sources, this analysis describes in detail the legal and administrative practices of the Tibetan Empire (c.600-c.850). Among the topics covered by this analysis are historical geography and the 'nationalisation' of clan territory, social stratification, technological innovation and legal culture. The Section on Law and State is not limited solely to law and administration, however, and also offers insights regarding cultural institutions such as religious practices and Tibetan funerary culture. Taken together, the scattered and fragmentary catalogues that make up the Section on Law and State, many of which ultimately derive from manuals and official records from the imperial period, constitute a rare juridical corpus of the Tibetan Empire. As such, it furnishes important and detailed information about the legal and administrative culture of the Tibetan Empire, and constitutes a fundamental source for Tibetan social history. The preservation of such documents within Tibet's postdynastic religious histories underlines the persistence of Tibetan political theory, according to which divine rulers, Buddhist or otherwise, must govern according to the just traditions of their forebears.